Technology as an instrument to measure the school cohabitation - Correa Romero, Nelsón Javier; Hernández Pineda, Luz Mireya (Universidad Pedagógica y Tecnológica de Colombia, 2010)
To face the enormous social changes that are underway, the assertive communication is of a great importance for the human coexistence, therefore, it is vital the search for novel ways to mediate among the forms of interactions generated from the services internet is offering. Through participant observations, interviews, analysis of documents and diverse strategies to innovate the coexistence, it is possible to establish “Technology as a mediate instrument for the school coexistence”, which uses the modern communication as a tool to face the school conflicts among equals, and as a way of active participation.